A Two-Key Access Control Scheme Based on Binary Access Mode - Islam, Md. Rafiqul; Selamat, Harihodin; Md. Sap, Mohd. Noor (Malaysian Journal of Computer Science, 2000)
A two-key access control scheme is proposed for implementing the access control matrix. The proposed scheme is based on binary form of access rights and time stamp concept. In this scheme each user is assigned one key and each file is also assigned one key. The key of a user or file can be used to derive the access rights to the files depending on the value of time stamp number. The scheme achieves full dynamism. That means, it can easily handle the dynamic access control problem, such as changing access right, adding a user or file and deleting a user or file.